Recent Trends in Household Financial Behaviour - Santos, Ana C. (2016)
This paper identifies general patterns of household financial behaviour for three groups of countries: The Early Financialisers, the Economic and Monetary Union Core and the Latecomers. Even though they stand in different positions as regards the development of their respective financial systems and household engagement with finance, there is a shared trend of growth of household debt and financial wealth, denoting common institutional changes across Europe and thus the systematic character of financialisation as an overall process of transformation of the economy and society. The evolution of pension and life insurance funds is highlighted, becoming the second most important financial asset held by households. This underlines the role of reforms of pension systems in promoting household financial relations, more than a shift towards investment in capital markets stimulated by new investment opportunities supplied by finance. Despite the exposure of private schemes to the financial turmoil, the current crisis has presented itself as an opportunity to bring the pension reform agenda even further forward. However, the trend towards the privatisation of social protection systems, enhancing individual responsibility through growing access to financial markets, must be assessed against the background of greater levels of unemployment and increasingly precarious employment relations that undermine it.